Caracterização das Recomendações de Streams na Twitch para o Público Infantil e Adolescente no Brasil e nos Estados Unidos - Gonçalves, Kênia C.; Soriano, Flávio; Vimieiro, Renato; Marques-Neto, Humberto T.; Almeida, Jussara M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
Twitch is a livestream sharing and interaction platform that strongly attracts young audiences due to its strong gaming presence. When watching a livestream, users see a list of channels with live streams suggested by the platform. In this study, we used the concept of personas (aged 13, 15, and 18) to represent the child and adolescent audience on Twitch, to simulate their access in Brazil and the United States, and to characterize the recommendations to this audience in both countries. Our personas watched live streams of a set of popular games, and for each stream watched, we collected the suggested streams for more than a month for each persona. Our results highlight and fill a gap in the literature: the presence of inappropriate content in these platform suggestions for children and adolescents, including rewards, games with inappropriate age ratings, advertisements, tags, and titles with inappropriate words. Our results can contribute to fostering public policies and computational improvements that contribute to a safer user experience within social media for children and adolescents.